Statements on Demand Using XSL-FO online presentation that offers better quality. - Lovell, Douglas
We encounter many statements and reports in our day-to-day lives. Phone bills, utility bills, bank statements and investment account statements are a few examples. More and more, the companies that produce these statements are making them available online, on demand through the Web. Some companies now offer incentives for customers to accept online statements in lieu of printed statements delivered through the mail; customers who want a printed record must print it locally.